Evaluation of Oxidative Stability of Compound Oils under Accelerated Storage Conditions - Pazzoti, Geisa [UNESP]; Souza, Camila [UNESP]; Veronezi, Carolina [UNESP]; Luzia, Debora; Jorge, Neuza [UNESP] (Inst Tecnologia Parana, 2018)
The oxidative stability of linseed (L), cotton (A), and coconut (C) oils, as well as of linseed: cotton (LA), linseed: coconut (LC), and linseed:cotton:coconut (LAC) compound oils was evaluated under accelerated storage at 60 degrees C/20 days. Coconut oil showed to be rather stable, mainly due to low levels of peroxides, conjugated dienes, p-anisidine, and long induction period. In addition, along with cotton oil, it improved the stability of linseed oil in the formulation of LAC compound oil. As to fatty acid profile, the compound oils showed to be composed mainly by unsaturated fatty acids. Cotton and coconut oils presented higher retention of total phytosterols, 78.87 and 76.16%, respectively, after 20 days of storage, when compared to linseed oil. The highest retention of total tocopherols at the end of storage was observed in LA (90.81%). In relation to antioxidant activity, by the DPPH method, with the increase in storage time, a reduction in the antioxidant substances of linseed, LC, and LAC oils was observed. Through the FRAP method, oscillations were observed, especially in linseed and compound oils. Although the oils were degraded over time, it was possible to verify that cotton and coconut oils contributed to increase the stability of linseed oil, which, in turn, raised the levels of coconut oil bioactive compounds.
Keywords: linseed; cotton; coconut; lipid oxidation; vegetable oils